MENINGKATKAN KINERJA KARYAWAN MELALUI DISIPLIN KERJA, TRAINING KERJA DAN JOB STRESS - Ika Rahayu Ningsih; Rini Handayani (STIE Atma Bhakti, 2018)
This study examines the significance of the influence to work discipline, job training and job stress on employee performance, and knows the variables that most influence the performance of PT Pan Rama Vista Garment in Sukoharjo as well. The number of samples is 50 people with sampling techniques using convenience techniques. The analysis technique used is multiple regression analysis with SPSS 23. Analysis on t test obtained t count> t table for work discipline variables and job stress which means that each of these variables individually influences employee performance, but for work training variables t count